2015
DOI: 10.1155/2015/347861
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Property ofPlantago majorLeaf Extract Reduces the Inflammatory Reaction in Experimental Acetaminophen-Induced Liver Injury

Abstract: Hepatic injury induces inflammatory process and cell necrosis. Plantago major is traditionally used for various diseases. This study aimed to determine the anti-inflammatory property of P. major leaf extracts on inflammatory reaction following acetaminophen (APAP) hepatotoxicity. Thirty male Sprague-Dawley rats were divided into 5 groups, namely, normal control (C), APAP, aqueous (APAP + AQ), methanol (APAP + MT), and ethanol (APAP + ET) extract treated groups. All APAP groups received oral APAP (2 g/kg) at da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
3
16
0
2
Order By: Relevance
“…This study also observed that highest anti-inflammatory activity was found in the ME at a dose of 900 mg/kg. This result was similar to the findings of Beara et al [18] and Hussan et al [38]. It is reported that anti-inflammatory activity of P. major is contributed by flavonoids such as baicalein and hispidulin and iridoid glycosides such as aucubin [8].…”
Section: In Vivo Anti-inflammatory Activitysupporting
confidence: 91%
“…This study also observed that highest anti-inflammatory activity was found in the ME at a dose of 900 mg/kg. This result was similar to the findings of Beara et al [18] and Hussan et al [38]. It is reported that anti-inflammatory activity of P. major is contributed by flavonoids such as baicalein and hispidulin and iridoid glycosides such as aucubin [8].…”
Section: In Vivo Anti-inflammatory Activitysupporting
confidence: 91%
“…The increased level of TNF-α makes TNF-α to bind to its receptor TNF-α receptor 1 (TNF-R1), which drives the activation of hepatic apoptosis and necrosis signaling (Chao, Wang, & Ding, 2017;Filliol et al, 2016). Inhibition of proinflammatory cytokines production attenuates inflammation-mediated hepatocyte injury following APAP toxicity (Devkar et al, 2016;Hussan et al, 2015). The levels of IL-6 and IL-12 F I G U R E 2 Effects of silkworm pupa oil on hepatic histology (original magnification 100×).…”
Section: Discussionmentioning
confidence: 99%
“…[23] Foliar extracts of P. major reduce the levels of pro-inflammatory cytokines (IL-1 , IL-1 , TNF-) released by activated macrophages may be due to local production of glucocorticoids. [29,55] Plantamajoside, several polyphenols and polysaccharides present in P.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Plant extracts of aerial or root organs present complex mixtures containing phenolic compounds, essential oils, alkaloids, among others, with synergistic effects among the different phytochemicals potentiating their action in multiple targets, and the possibility of a loss of bioactivity and chemical instability if isolated. Widely used for therapeutic purposes in traditional medicine, medicinal plants of Achyrocline satureioides, [19][20][21] Cinnamomum camphora, [22][23][24][25][26][27] Myroxylon peruiferum, [28] Plantago major, [2,[29][30][31][32][33] Vernonia polyanthes inflammatory potential of polyphenolic compounds, in particular flavonoids, is in its action in the various cells involved in the inflammatory process as granulocytes, macrophages, lymphocytes, mast cells, epithelial cells, endothelial cells, dendritic cells and fibroblastos, in modulating the expression of pro-inflammatory enzymes such as cyclooxygenase, lipoxygenase, nitric oxide synthases responsible for the production of mediators such as nitric oxide, prostanoids, leukotrienes, chemokines or adhesion molecules, and several key cytokines, essentially through signaling nuclear factor-kappa B and mitogen-activated protein kinase.…”
Section: Introductionmentioning
confidence: 99%